2010
DOI: 10.1515/rose.2010.010
|View full text |Cite
|
Sign up to set email alerts
|

Existence and optimality conditions in stochastic control of linear BSDEs

Abstract: We consider control problems for systems driven by linear backward stochastic differential equations (BSDEs). We prove the existence of strict optimal controls under the convexity of the control domain as well as the cost functional. Our approach is based on strong convergence techniques for the associated linear BSDEs. Moreover, we establish necessary as well as sufficient conditions of optimality, satisfied by an optimal strict control. The proof of this result is based on the convex optimization principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Then, Bahlali and al. [1] investigate a control problem, with a general cost functional by using probabilistic tools. The authors suppose that the generator is linear and assume convexity of the cost function, as well as the action space.…”
Section: Introductionmentioning
confidence: 99%
“…Then, Bahlali and al. [1] investigate a control problem, with a general cost functional by using probabilistic tools. The authors suppose that the generator is linear and assume convexity of the cost function, as well as the action space.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there has been much literature on BSDE control system driven by Brownian motion (see e.g. [2,3,5,11,10]). But to our best knowledge, there is no discussion on the optimal control problem of BSDE driven by Teugel martingales and an independent Brownian motion, which motives us to write this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The case of an SDE where the diffusion coefficient depends explicitly on the control variable has been solved in El Karoui et al (1987);Haussmann (1986), where the optimal relaxed control is shown to be Markovian, see also Haussmann and Lepeltier (1990); Mezerdi and Bahlali (2002); Bahlali et al (2006). Existence results for systems driven by backward and forward-backward SDEs have been investigated in Bahlali et al (2010Bahlali et al ( , 2011Buckdahn et al (2010).…”
mentioning
confidence: 99%